Researching Understandings of the Child in Intercultural Marriages: Trying Out a Hermeneutic Interview Protocol - Tine, Janine; Ellis, Julia (Alberta Journal of Educational Research, 2022)
In interpretive inquiry, researchers need interviewing approaches that will create possibilities for insight and holistic understanding. A hermeneutic interview protocol was developed and refined over a number of years in the context of an interpretive inquiry course. In this study, one of the authors examines her experience with using this interview framework in a practice inquiry for her research on “understandings of the child” in intercultural marriages. The study identifies the misgivings and doubts she experienced before and during the interview. It also illustrates how the structure of the interview supported the interview participant in reflecting upon and reconstructing his experience and supported the researcher in accomplishing a fusion of horizons. The interview framework invited stories from different important contexts and having stories from across time, place, and activity enabled the researcher to identify themes. Clarity about themes meant that important stories could be interpreted with more confidence. Keywords: hermeneutics; pre-interview activities; case studies; interpretive inquiry; open-ended interview questions Dans le cadre d'une enquête interprétative, les chercheurs ont besoin d'approches aux entrevues qui créent des possibilités de compréhension holistique et de vision. Un protocole d'entrevue herméneutique a été développé et affiné pendant plusieurs années dans le contexte d'un cours sur l'enquête interprétative. Dans cette étude, l'une des auteures examine son expérience de l'utilisation de ce cadre d'entrevue dans une enquête pratique pour sa recherche sur les "conceptions de l'enfant" dans les mariages interculturels. L'étude identifie les réticences et les doutes qu'elle a éprouvés avant et pendant l'entrevue. L’étude illustre également dans quelle mesure la structure de l'entrevue a aidé le participant à réfléchir et à reconstruire son expérience et a aidé la chercheure à réaliser une fusion des horizons. Le cadre de l'entrevue invitait à raconter des histoires provenant de différents contextes importants et le fait d'avoir des histoires à travers le temps, le lieu et l'activité a permis à la chercheure d'identifier des thèmes. La précision des thèmes a permis d'interpréter les histoires importantes avec plus de confiance. Mots clés : herméneutique ; activités de pré-entrevue ; études de cas ; enquête interprétative ; questions d'entrevue ouvertes